SALNAMELERE GÖRE DİYARBAKIR VİLAYETİNDE DİNİ VE SOSYAL YAPI - BAYDUR, ŞENGÜL (Fırat Üniveristesi, 2007)
Osmanlı eyalet merkezlerinden biri de Diyarbakır'dır. Bölge uzun yıllarAnadolu medeniyetlerine ev sahipliği yapmıştır. Diyarbakır ve çevresinde Musevi,Hıristiyan ve Müslümanlar yüzyıllar boyunca huzur içerisinde bir arada yaşamıştır.Diyarbakır vilayetinin geneline baktığımızda dini grupların kendilerineait okulları ve ibadethanelerinin her dönem varlığını sürdürdüğünü tespit etmekteyiz.Vilayet Salnamelerine ve Maarif Salnamelerine göre Müslümanların dini ve sosyalkurumlarının yanında Gayrimüslimlerin de kendilerine ait dini ve sosyal kurumlarıvardır.Diyarbakır vilayetinde yaşayan toplam nüfusu Müslim, Gayrimüslimoranlamasıyla merkezden başlamak şartıyla sancak ve kazalar şeklinde tablolar halindevererek bölgede dini grupların nüfusları ortaya konmuştur.Anahtar kelimeler: Diyarbakır, Müslüman, Gayrimüslim, Sosyal ve dinikurum, Nüfus.

Diyarbakır was one of the centres of Ottoman states. The city hostedAnatolian civilisation for many years. Musevi, Christians and Muslims lived together inpeace for many years and this condition continued throughout the sovereignty of Islamaround and in Diyarbakır. Several multi-religious and distinct cultures lived together inthe region.When we look at the province of Diyarbekir as a whole, we see thatevery school and sanctuary belonging to religious groups existed in every period oftime. According to Province Yearbook and Education Yearbook, besides the religiousand Social institutions of Muslims, non-Muslims also had their own religious and socialinstitutions.We tried to reflect the population of religious groups living in the regionwith comparing the whole population and Muslim and non-Muslim population inDiyarbakır from the center to subdivisons and sanjaks of the province as tables.Key Words: Diyarbakır, Muslim, non-Muslim, Social and ReligiousInstitues, Population.
Province yearbook religions and social structure in the province of Diyarbakir during the second half
Keywords: Din